The Effect of E-Recruitment Effectiveness, Compensation, and Career Development on Job Application Interest Among Generation Z in Medan, with Company Reputation as an Intervening Variable - Putri, Wanda Anisya; Absah, Yeni; Sembiring, Beby Karina Fawzeea (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study analyzes the influence of online recruitment, compensation, and career development on the interest in applying for jobs of Generation Z in Medan City in companies with company reputation as an intervening variable. Using a quantitative approach with 398 samples of final year students of State Universities in Medan City. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with Partial Least Square (PLS). The results show that corporate reputation, career development, e-recruitment, and compensation have a positive and significant effect on the interest in applying for jobs of generation Z. Company reputation can mediate the relationship between online recruitment, compensation, and career development on interest in applying for jobs. This study provides recommendations to improve the effectiveness of online recruitment, compensation, career development and company reputation.Unemployment among Generation Z has become a critical issue requiring special attention. According to the National Labor Force Survey as of February 2024, approximately 3.6 million Generation Z were unemployed. Compared to Indonesia's total open unemployment of 7.2 million people, Generation Z accounts for about 50% of the total unemployment. This study analyzes the effect of E-recruitment, compensation, and career development on job application interest among Generation Z in Medan, with company reputation as an intervening variable. A quantitative approach was employed, involving 398 final-year students from public universities in Medan. Data were collected through questionnaires and analyzed using SEM-PLS. The results indicate that the most influential variable is company reputation, followed by career development, E-recruitment, and, lastly, compensation. Additionally, company reputation mediates the relationship between E-recruitment, compensation, and career development with job application interest. This study provides recommendations for enhancing the effectiveness of E-recruitment, compensation, career development, and company reputation.